Safety and Efficacy of i-FACTORTM Bone Graft in Anterior Cervical Discectomy and Fusion: A Prospective, Randomized, Controlled, Multi-Center, Investigational Device Exemption Study. Issue 1 (April 2016) - Janssen, Michael; Arnold, Paul; Sasso, Rick; Fehlings, Michael; Patel, Ashvin
Introduction: The objective of the study was to evaluate i-FACTOR Putty and local autologous bone in a non-inferiority model when applied in instrumented ACDF using a structural allograft ring in subjects with cervical degenerative disc disease. I-FACTOR Putty is a composite bone graft material consisting of a synthetic peptide (P-15) adsorbed onto anorganic bone mineral (ABM). The P-15 fragment is a short chain peptide that mimics a cell binding domain of Type I collagen, that facilitates cell attraction, attachment and activation on the ABM scaffold. Material and Methods: A prospective, randomized, controlled, multi-center trial was designed to investigate the safety and efficacy of i-FACTOR Putty against an autograft control group. The pre-determined statistical plan was that the i-FACTOR Putty was non-inferior to autologous bone. Twelve-month evaluations were considered to be the primary endpoint. Primary endpoints chosen for the purpose of this study included radiographic evidence of fusion, neurological, outcomes, functional outcomes, and assessment of complication rates. A blinded, independent third party was utilized to assess safety, radiologic outcomes, and neurologic outcomes. Adult patients with radiographic evidence of degenerative disc disease and with evidence of a history of arm/shoulder pain, decreased reflexes, decreased strength, and/or abnormal sensation were randomized for inclusion in this trial. Surgeons performed an anterior cervical discectomy. The control arm received an allograft ring filled with autologous bone. The investigational arm received an allograft ring filled with i-FACTOR Putty. Successful arthrodesis was based upon radiographic examinations and neck disability index (NDI) was scored as the absolute difference between the baseline and the 12-month scores. Neurological status was determined by comparing the preoperative status to maintenance or improvement over the twelve-month period. Adverse outcomes were also assessed. Overall success was judged by success in all primary endpoints. Results: A total of 313 patients participated in the study (161 pts.-i-FACTOR Putty: 152 pts.-Autologous bone). Preoperative patient demographics were statistically similar in both populations. The study demonstrated the non-inferiority of i-FACTOR Putty compared with autologous bone for fusion status, change in NDI, and neurological success at 12 months. Fusion rates were 89% in the i-FACTOR Putty group and 86% in the Autologous bone group ( p = 0.0004 for non-inferiority test). NDI scores improved a mean of 29 points in the i-FACTOR Putty group and 27 points in the Autologous bone group ( p < 0.0001 for non-inferiority test). The neurological success rates was 94% in the i-FACTOR Putty group and 93% in the Autologous group ( p < 0.0001 for non-inferiority test). The proportion of subjects with any adverse event at 12 months was not different between both groups ( p = 0.8814). The overall success rate was significantly higher in the i-FACTOR Putty group than the Autologous bone group. The proportion of subjects who achieved fusion success, NDI success, neurological success, and safety success was 69% in the i-FACTOR Putty group and 58% in the Autologous bone group ( p = 0.0382). Conclusion: In summary, the above data strongly support the safety and effectiveness of i-FACTOR Putty for its anticipated intended use. The i-FACTOR Putty subjects demonstrated a high rate of fusion, improvement in pain and function, similar adverse event rates to the Control group, and a low rate of subsequent surgeries or device-related adverse events.